Effect of light stress and concentrations of nitrogen and carbon in the production of phytonutrients in the microalga Scenedesmus obliquus (Chlorophyceae, Chlorococcales) - Zapata, Luz Marina (2020)
Under stress conditions microalgae produce phytonutrients. However, it is necessary to determine the environmentalconditions that stimulate phytonutrient biosynthesis. We evaluate growth kinetic models and the influence of sodium nitrateand sodium acetate concentrations, as well as the irradiance in the production of total carotenoids, total phenols and proteinsin culture of Scenedesmus obliquus (Turpin) Kützing. The microalga was cultivated in Arnon medium in bioreactors with a 16:8light-darkness photoperiod. When the stationary phase was reached, sodium acetate (0, 2.5, 5 g/L) and sodium nitrate (0.27,44.00, 87.73 g/L) were incorporated and the irradiance [36.7, 69.5, 102.3 µmol/(m2s)] was modified to generate stressconditions. Growth was successfully predicted by the Gompertz model. The maximum content of protein was 4.92 mg/g dwcand of total phenols was 2.31 mg/g dwc using 2.5 g/L sodium acetate, 44 g/L sodium nitrate and irradiance of 65.9 µmol/(m2s).The maximum production of total carotenoids was 374.30 mg -carotene/g dwc with 5 g/L of sodium acetate, 0.27 g/L ofsodium nitrate and irradiance of 65.9 µmol/(m2s). The results showed that this microalga has potential application in the foodindustry in order to improve its nutritional and functional properties.